PELUANG DAN TANTANGAN BIG DATA SEBAGAI METODE DALAM KAJIAN KOMUNIKASI (Sebuah Kajian Literatur) - Islami, Farina (Lembaga Penerbitan Universitas Esa Unggul, 2024)
The utilization of big data is still not very popular in Indonesia, especially among communication researchers. In reality, big data is beneficial for effective and efficient data collection, which can facilitate researchers in obtaining data. Big data in communication studies has garnered significant interest from both academics and business professionals in recent years. This paper is a literature review with a traditional conceptual approach. The primary data in this writing consists of previous research journals discussing the opportunities and challenges of big data in social studies, which were subjectively selected by the researcher. The study results indicate that the opportunity of using big data as a method in communication research is to facilitate data collection and a broader examination of communication contexts related to media and technology, such as sentiment analysis in political communication, image analysis in organizational communication, consumer needs analysis in marketing communication, and predictive analysis in disaster communication. Challenges that arise include data accountability, especially in evaluating sentiment, opinions, and images through mass media. Furthermore, the statistical nature of big data raises doubts about data accuracy. However, these shortcomings can be optimized with competent human resources and integrated, standardized big data support tools provided by the government and relevant stakeholders.Keywords: Big data, Communication, Opportunities, Challenges.